Updates on COVID-19 control and vaccination campaigns (COVID-19 and non COVID-19) - Signorelli, Carlo; Odone, Anna (Acta Biomedica Atenei Parmensis, 2021)
Years 2020 and 2021 have been a historic turning point in Italian and international vaccination policies (1). In fact, on the one hand, during the most violent phases of the COVID-19 pandemic, there was a drop in the immunization programmes of the National Immunization Prevention Plan 2017-19 (2), on the other hand, mass immunization campaigns against SARS-CoV-2 had an unexpected success, especially in our country. COVID-19 vaccine coverage rate of around 90% in subjects over 12-year allowed us to be among the first countries in Europe, with significant reductions in severe forms of COVID-19 as early as the summer of 2021 (3). [...]